Multiplex ligation reaction based on probe melting curve analysis: a pragmatic approach for the identification of 30 common Salmonella serovars - Zuo, Le (Ann Clin Microbiol Antimicrob, 2019)
BACKGROUND: While Salmonella serotyping is of paramount importance for the disease intervention of salmonellosis, a fast and easy-to-operate molecular serotyping solution remains elusive. We have developed a multiplex ligation reaction based on probe melting curve analysis (MLMA) for the identification of 30 common Salmonella serovars. METHODS: Serovar-specific primers and probes were designed based on a comparison of gene targets (wzx and wzy encoding for somatic antigen biosynthesis; fliC and fljB for flagellar antigens) from 5868 Salmonella genomes. The ssaR gene, a type III secretion system component, was included for the confirmation of Salmonella. RESULTS: All gene targets were detected and gave expected Tm values during assay evaluation. Cross reactions were not demonstrated between the 30 serovars (n = 211), or with an additional 120 serovars (n = 120) and other Enterobacteriaceae (n = 3). The limit of identification for all targets ranged from using 1.2 ng/μL to 1.56 ng/μL of DNA. The intra- and inter-assay standard deviations and the coefficients of variation were no more than 0.5 °C and less than 1% respectively, indicating high reproducibility. From consecutive outpatient stool samples (n = 3590) collected over a 10-month period at 11 sentinel hospitals in Shenzhen, China, we conducted a multicenter study using the traditional Salmonella identification workflow and the MLMA assay workflow in parallel. From Salmonella isolates (n = 496, 13.8%) derived by both workflows, total agreement (kappa = 1.0) between the MLMA assay and conventional serotyping was demonstrated. CONCLUSIONS: With an assay time of 2.5 h, this simple assay has shown promising potential to provide rapid and high-throughput identification of Salmonella serovars for clinical and public health laboratories to facilitate timely surveillance of salmonellosis.